Chondroitin sulfate n-acetylgalactosaminyltransferase-2 (ChGn-2) plays a significant role in cardiac remodeling and heart failure following pressure overload. (14th October 2021) - Haryono, A; Ikeda, K; Nugroho, D B; Kitagawa, H; Igarashi, M; Hirata, K; Emoto, N
Abstract: Background: Cardiac extracellular matrix (ECM) is critically involved in cardiac homeostasis by providing mechanical support as well as modulating growth factor signaling. Cardiac ECM dysregulation has been shown in heart failure pathogenesis, and accumulation of chondroitin sulfate glycosaminoglycans (CS-GAGs) was previously shown to exacerbate heart failure by augmenting inflammation and fibrosis at the chronic phase. However, it remains unclear whether and the mechanism by which CS-GAGs cause cardiac dysfunction, especially at the acute phase. Purpose: The purpose of this study is to elucidate the role of CS-GAGs in heart failure. Methods: In this study, we analyzed the role of CS-GAGs in heart failure using mice with target deletion of chondroitin sulfate N-acetylgalactosaminyltransferase (ChGn)-2 that elongates CS chains of GAGs. Heart failure was induced by transverse aortic constriction (TAC) in mice. Since cardiac fibroblasts (CFs) are the primary cells for ECM production in the heart, we explored the role of CF-derived ECM in cardiomyocyte apoptosis. CFs were given stretch stimuli that mimic pressure overload conditions. Results: Significant CS-GAGs accumulation was detected in the heart of WT mice after TAC, which was substantially reduced in the heart of ChGn2−/− mice. Unexpectedly, loss of ChGn-2 deteriorated left ventricular systolic dysfunction accompanied by augmented cardiac hypertrophy and increased cardiomyocyte apoptosis. Stretch stimuli increased ChGn-2 expression and enhanced GAG production in CFs. Interestingly, only conditioned medium (CM) derived from stretched CFs showed protective effects on cardiomyocyte death induced by doxorubicin. Degradation of CS-GAGs in CFs-derived CM by using Chondroitinase ABC abolished its cardioprotective effect. Further experiments revealed that this cardioprotective effect is at least partially through CS-GAGs-derived PI3K/AKT pathway activation via CD44. Conclusion: Our data revealed that CF-derived GAGs protect cardiomyocytes from death in the acute phase of heart failure due to pressure overload; thus, insufficient GAGs production caused by loss of ChGn-2 exacerbated heart failure. Funding Acknowledgement: Type of funding sources: None.